Implementasi Kurikulum Merdeka: Pembelajaran Profil Pelajar Pancasila Di TK Paramata Bunda Palopo - Klaramita, Klaramita; Sabani, Fatmaridah; Kamariah Hasis, Pertiwi (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2025)
The Independent Curriculum provides freedom to teachers and students in shaping character to create a fun and meaningful learning environment. This study discusses the Implementation of the Independent Curriculum in Learning the Pancasila Student Profile at Paramata Bunda Palopo Kindergarten. This study aims: 1) to determine the Implementation of the Independent Curriculum in Learning the Pancasila Student Profile at Paramata Bunda Palopo Kindergarten, and 2) to determine the supporting and inhibiting factors of the Independent Curriculum in Learning the Pancasila Student Profile at Paramata Bunda Palopo Kindergarten. This study uses qualitative research with a descriptive approach. The research subjects consisted of the principal and 1 teacher. Data collection techniques were obtained through observation, interviews, and documentation. The analysis technique used the Miles and Huberman model through data reduction, data presentation and concluding. The results of the study indicate that the Implementation of the Independent Curriculum in learning the Pancasila student profile at Paramata Bunda Palopo Kindergarten has run optimally. Teachers have integrated character values into daily learning in a creative and fun way. The main supporting factors in the implementation of the Independent Curriculum are school support, teacher training, collaboration between teachers and the principal, parental involvement, and internet access. Inhibiting factors include limited time for preparation, parents' lack of understanding of the importance of the Independent Curriculum and adaptation to the new curriculum, and teachers' competencies that still need to be improved. The implementation of the Independent Curriculum can improve the quality of learning and the character development of Pancasila students at Paramata Bunda Kindergarten, Palopo